Infant And Young Child Feeding Practices and Infections Pattern in Children Up To 24 Months Age Attending Outdoor Patient Department of a Tertiary Care Hospital of South Gujarat - Choraria, Nirmal; Patni, Mohamed Anas; Vaidya, Jigesh; Nimavat, Harita; Akikwala, Mushirabanu (National Journal of Community Medicine, 2023)
Background: Optimal infant and young child feeding practices (IYCF) are effective public health intervention to enhance child survival, nutrition and development. There is also documented evidence regarding the protective effect of optimal IYCF practices against diarrhea and ARTI. Objectives: 1) To assess knowledge and practices regarding IYCF among study participants. 2) To explore the association of feeding practices of mothers with the morbidities (infections) in their children. Methodology: The present study was a hospital based cross-sectional study, carried out during September 2019 to March 2021. A total of 380 mothers of children less than two years attending OPD of Institute of child health, Nirmal hospital private limited, a tertiary care multi-specialty hospital were interviewed using pre-designed and pretested questionnaire. Results: Feeding practices during early days of life to be reasonably good among study participants with almost 2/3rd of the study participants practicing them. Mean number of morbidity episodes requiring consultation were significantly lower in the children whose mothers practiced optimal IYCF practices. Conclusion: Satisfactory knowledge and practices were observed among study participants regarding various infant and young child feeding practices. Poor feeding practices in children had significant association with morbidity episodes of diarrhea and ARTI in children.